2011
DOI: 10.1007/s11854-011-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Limit-periodic Schrödinger operators with uniformly localized eigenfunctions

Abstract: We exhibit limit-periodic Schrödinger operators that are uniformly localized in the strongest sense possible. That is, for these operators there are uniform exponential decay rates such that every element of the hull has a complete set of eigenvectors that decay exponentially off their centers of localization at least as fast as prescribed by the uniform decay rate. Consequently, these operators exhibit uniform dynamical localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…All other operator families that are known to be localized (random potentials, strongly coupled quasi-periodic potentials or skew-shift potentials) are either not known to be uniformly localized or known to be not uniformly localized. Motivated by [71] and extending [135], Han [125] showed that phase uniformity is a general phenomenon in the context of uniform localization.…”
Section: 3mentioning
confidence: 99%
“…All other operator families that are known to be localized (random potentials, strongly coupled quasi-periodic potentials or skew-shift potentials) are either not known to be uniformly localized or known to be not uniformly localized. Motivated by [71] and extending [135], Han [125] showed that phase uniformity is a general phenomenon in the context of uniform localization.…”
Section: 3mentioning
confidence: 99%
“…It is however possible to prove pure point spectrum uniformly across the hull in certain scenarios (which are not dense). This follows from a combination of works of Pöschel [53] and Damanik-Gan [17].…”
Section: Pure Point Spectrummentioning
confidence: 99%
“…In this paper we will answer this question which arose naturally from the known results, and which was asked in print on several occasions (e.g., [14,18]). Theorem 1.1.…”
Section: Introductionmentioning
confidence: 94%